Zoneamento da dinâmica costeira - aplicação de geotecnologias em apoio à gestão costeira integrada na praia Atalaia-PA e trecho de praias entre os municípios de Guamaré e Macau-RN - Busman, Débora Vieira (2016)
Climate change on the coastal zone causes impacts such as inundation, coastal erosion, storm surges and heatwaves and have resulted in millions of dead, billions of injured people and billions of dolars in economic losses. Brazil is among the top ten countries affected by climate change and the North and Northeast regions will suffer most of the impacts. In order to study the socioeconomic vulnerability of coastal counties of Macau and Guamaré/RN (NE of Brazil) and Salinópolis/PA (N of Brazil), which are exposed to different environmental and social-economics dynamics, were applied four indexes of Socioeconomic Vulnerability. Guamaré was the county with highest vulnerability in the first three methods and Salinópolis was the most vulnerable in the fourth method. Therefore, the economic profit obtained with industries installed in Macau and Guamaré is not generating greater social development, then the services sector of Salinópolis. This research also identified which variables would be used in physical vulnerability index, and reduced the subjectivity in the choice of them. The coastal counties of Macau and Guamaré feature multiple conflicts of land use/land cover since the main economic activities consist in the oil and gas industries, salt and shrimp farming, and wind power installed in segments of great environmental susceptibility to climate change impacts. Salinópolis had greater coastal vulnerability because haven‘t sustainable shoreline management policies, and the shoreline is partially occupied by houses where the coastal dynamics are strong, resulting in constantly spent on coastal protection. The areas under greatest risk and criticality to flooding were the urban areas, where are the main economic activities, and mangrove areas. Projections indicated that in these counties hundreds to thousands of people will be at flooding risk until 2100, resulting in environmental and socio-economic losses at hundreds or even millions of dollars. These results may support the decision-making process for environmental managers and tested methods are replicable in both coastal as inner couties.